PERBANDINGAN LEKSIKON DIALEK BAHASA JAWA BREBES DI KECAMATAN SIRAMPOG DENGAN BAHASA JAWA STANDAR YOGYA-SOLO - Rizal, Ghulam Arif; Wakhyudi, Yukhsan (DIALEKTIKA JURNAL PENDIDIKAN BAHASA INDONESIA, 2024)
The research aims to compare the Javanese lexicon of the Brebes dialect in Sirampog sub-district and analyze variations in the lexicon with standard Javanese in Yogya-Solo. This research method is descriptive analysis using an interactive model. The method used in this research is divided into three stages, namely the data provision stage, the data analysis stage, and the data analysis results presentation stage. As a result of the research, differences in the lexicon variations of the Brebes Javanese dialect in Sirampog sub-district and the standard Javanese language of Yogya-Solo, both phonetic and phonemic, researchers found several aspects, which include; kinship speech, body parts lexicon, number word lexicon, house lexicon and its parts, animal lexicon and its parts, disease lexicon, verb and movement lexicon, time lexicon, nature lexicon, and nature and condition lexicon. The phonological and lexical influence of the Brebes Javanese language in Sirampog sub-district is influenced by Sundanese, Tegal dialect and Banyumas dialect. Key words: Javanese language, lexical variations, Brebes Javanese dialect, Sirampog